Comparative Analysis Study and Response Strategies in the Role of Biomass Energy in Redefining Global Influence: A Study on the United States and China - Dang, Enqi (Transactions on Economics, Business and Management Research, 2024)
This research delves into the comparative development of biomass energy strategies in the United States and China, emphasizing their critical role in global renewable energy transitions. It highlights the increasing importance of biomass energy amid the imperative shift towards sustainable energy sources driven by climate change concerns and geopolitical dynamics. Through a thorough analysis of policy frameworks, technological innovations, and market implementations, the study identifies key similarities and differences in the approaches of both countries. While both nations prioritize reducing dependence on fossil fuels and promoting environmental sustainability, they diverge in their policy incentives, technological research, and resource utilization strategies. The paper suggests avenues for enhancing biomass energy development, including strengthening policy support, fostering technological innovation, and promoting international cooperation. Ultimately, the research of this paper underscores the significance of biomass energy in achieving sustainable energy transitions and emphasizes the importance of collaborative efforts between nations in addressing global energy and environmental challenges.